Influence of Polyethylene Glycol Additive on Performance of Polysulfone and Polyethersulfone Membrane - Siti Hawa Mohamad; Hasan Zuhudi Abdullah; Maizlinda Izwana Idris; Zawati Harun; Ahmad Fauzi Ismail; Muhamad Zaini Yunos; Sulaiman Hasan (Journal of Mechanical Engineering and Sciences, 2014)
This paper focuses on the performance of polysulfone (PSf) and polyethersulfone (PES) ultrafiltration membranes with polyethylene glycol (PEG). The aim of this study is to determine the effect of PEG as an additive in producing PSf and PES membrane. The flat sheet membranes were prepared via a phase inversion method in which the casting dope solution consists of polysulfone and polyethersulfone separately as polymer, while N-methyl-2-pyrrolidone is used as the solvent material. PEG 400 was used as a pore forming additive in the casting dope solution. The morphology of membranes was analyzed by scanning electron microscopy. The performance of membranes was evaluated in terms of pure water flux (PWF) and humic acid rejection. The effect of different concentrations of PEG additive exhibits significant improvement on PSf and PES membrane performance. The results indicated that PES ultrafiltration membrane exhibits better performance in PWF than does PSf membrane. It was found that the pure water flux increases as the PEG concentration increases (0 to 8 wt%) in casting solution. As a result, the morphology of membranes prepared with a high concentration of PEG has a larger pore size. It can be concluded that PES ultrafiltration membrane consisting of PEG 400 yields an excellent increase in pure water flux compared to PSf membrane.